Cation exchange membrane, ion exchange membrane cell and electrodialyzer
The cation exchange membrane with zeolite and binder resin layers addresses the challenge of selectively concentrating ammonium ions, offering improved energy efficiency and selectivity in electrodialysis by leveraging zeolite's adsorbent properties and low ion exchange binder characteristics.
Patent Information
- Application Number
- JP2023096856
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ion exchange membrane technologies face challenges in selectively concentrating specific cations like ammonium ions while maintaining high energy efficiency, as they often suffer from scale formation, energy inefficiency, and membrane degradation due to the presence of other ions and contaminants.
A cation exchange membrane is developed with a cation exchange layer containing zeolite and a binder resin, optionally accompanied by another cation exchange layer, enhancing selectivity and energy efficiency by using zeolite's adsorbent properties and a binder with low ion exchange ability.
The membrane achieves high permselectivity for ammonium ions, improving energy efficiency and reducing unintended ion concentration, thereby enhancing the selective concentration of ammonium ions in electrodialysis processes.
Smart Images

Figure 2024178598000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cation exchange membrane, and an ion exchange membrane cell and an electrodialysis device using the same. [Background technology]
[0002] Technologies for concentrating and separating ions in wastewater include distillation, ion exchange and adsorption, reverse osmosis (RO) membrane, forward osmosis (FO) membrane, brine concentration (BC), electrodialysis (ED), and Donnan dialysis. Among these, distillation can handle a wide range of salt concentrations and water qualities and has excellent resistance to contamination, but requires a large amount of energy consumption and is particularly unsuitable for treating dilute solutions. For ion exchange and adsorption, various ion exchangers and adsorbents have been developed (e.g., Patent Document 1), but continuous operation is difficult because a regeneration process is required for the ion exchange material and adsorbent, and equipment and chemicals are required to regenerate the ion exchange material and adsorbent, making continuous treatment unsuitable. In the RO membrane method, ions are concentrated by applying a pressure equal to or greater than the osmotic pressure to the wastewater to dehydrate it, so concentration from a dilute solution requires high power costs. In addition, membrane cleaning and replacement are required frequently for wastewater containing membrane pollutants. In addition, concentration of high salt concentrations is difficult due to the membrane's pressure limit. The FO membrane method concentrates ions by dehydrating them, just like the RO membrane method. It has the advantage of not applying pressure and not needing electricity by using a driving force solute (DS), but otherwise has the same problems as the RO membrane. The Brine Concentration (BC) method can concentrate salts to higher concentrations than the RO membrane by connecting FO membrane modules in series in multiple stages, but it requires a larger membrane area than the RO membrane method because it refluxes part of the concentrated liquid. The Donnan dialysis method concentrates and separates ions using DS, just like the FO membrane method, so it does not require electricity, but it is necessary to separate the DS and the target ions. As mentioned above, each method has its own advantages and disadvantages, but since actual treated water contains not only impurities but also various ions, with the exception of the ion exchange method, there are problems with scale formation due to these ions and reduced energy efficiency for concentrating the desired ions.
[0003] The ED method is a technology for concentrating and desalination of ions using an ion exchange membrane. In the case of the concentration process, ions are moved and concentrated, so it is particularly effective when separating and concentrating specific trace ions in the presence of membrane foulants or ions other than the target. Although high-concentration salt treatment requires electricity, it is a technology that allows high-concentration treatment like the BC method. However, in the ED method, ions other than the target ions are also concentrated at the same time. In this case, when divalent cations such as calcium ions are concentrated, scale is formed in the membrane, on the membrane surface, or in the solution flow path, leading to membrane destruction and a decrease in system efficiency (see Non-Patent Document 1). In addition, when a cation with the same valence as the target ion, for example, ammonium ions, is targeted, if non-target monovalent ions such as Na ions and K ions are present, electricity is consumed to concentrate the non-target ions, which reduces the energy efficiency of separating and concentrating the target ions. Therefore, there has been a demand for the development of an ion exchange membrane that selectively transmits specific target ions such as ammonium ions.
[0004] Among cations, the separation and concentration of ammonium ions in particular has attracted attention, for the following reasons. Currently, nitrogen compounds in waste gases and wastewater are detoxified by spending a great deal of energy. However, there are cases where nitrogen compounds are released without being treated, or where the treatment is insufficient, which has a large impact on the environment. Therefore, there is a demand for the development of resource ammoniaization technology for nitrogen compounds in wastewater, which will realize the detoxification and resource recovery of these harmful nitrogen compounds derived from human activities (Clean Earth). For this reason, focusing on nitrogen compounds in wastewater, technology is being developed to convert them into ammonia (including ammonium ions) and concentrate them to make them into a form that can be used as a valuable resource (resource ammonia). Among these technologies, the separation and concentration of ammonium ions present in wastewater in an energy-saving manner has attracted attention. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-92822 A [Non-patent literature]
[0006] [Non-Patent Document 1] "Selective permeability of ions in ion exchange membranes," Asahi Glass Research Report 64 (2014), pp. 21-25 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a cation exchange membrane which has high selectivity for specific cations, particularly ammonium ions, and further has high energy efficiency during dialysis. [Means for solving the problem]
[0008] The present inventors began to study ion exchange membranes that have high selectivity for specific ions and high energy efficiency, and proceeded with the study of ion exchange membranes that have high selective permeability for ammonium ions as the specific ions of interest. In the course of the study, they found that a cation exchange membrane with high selective permeability for ammonium ions can be obtained by mixing zeolite particles and a binder resin to form a cation exchange layer and providing another cation exchange layer on one or both sides of the cation exchange layer. Zeolite is known as an adsorbent for ammonium ions, but it has not been commonly used as a cation exchange membrane. However, by adopting the above-mentioned configuration found by the present inventors, a cation exchange membrane using zeolite that has high selective permeability for specific cations, particularly ammonium ions, can be obtained, and a cation exchange membrane with high energy efficiency can be obtained. The present invention was thus completed.
[0009] That is, the present invention is specified by the following items. (1) A cation exchange membrane having a cation exchange layer containing zeolite and a binder resin, and another cation exchange layer provided on one or both sides of the cation exchange layer. (2) The cation exchange membrane according to (1) above, wherein the binder resin is a resin having no ion exchange capacity and / or a resin having a low ion exchange capacity. (3) An ion exchange membrane cell in which an anion exchange membrane and the cation exchange membrane described above in (1) or (2) are arranged opposite each other. (4) An electrodialysis apparatus comprising an anode, a cathode, a cation exchange membrane and an anion exchange membrane, the cation exchange membrane being the cation exchange membrane described above in (1) or (2). Effect of the Invention
[0010] The cation exchange membrane of the present invention has excellent selective permeability to specific cations, particularly ammonium ions. The ion exchange membrane cell of the present invention can be used in devices such as electrodialysis to selectively concentrate specific cations, particularly ammonium ions. The electrodialysis device of the present invention can selectively concentrate specific cations, particularly ammonium ions. The cation exchange membrane, ion exchange membrane cell, and electrodialysis device of the present invention can increase energy efficiency during dialysis. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing an example of the use of the ion exchange membrane cell of the present invention. [Diagram 2] FIG. 2 is a scanning electron microscope (SEM) image of the zeolite used in Example 1. [Diagram 3] FIG. 3 is an SEM image of a cross section of the zeolite membrane produced in the reference example. [Figure 4] FIG. 4 is a diagram showing the measuring device and measuring conditions for the membrane resistance used in the Examples, Reference Examples, and Comparative Examples. [Diagram 5] FIG. 5 is a diagram showing an electrodialysis test apparatus used in the Examples, Reference Examples, and Comparative Examples. [Figure 6] FIG. 6 is a diagram showing the results of an electrodialysis test of the reference example. [Figure 7] FIG. 7 is a diagram showing the results of the electrodialysis test of Example 1. [Figure 8]FIG. 8 is a diagram showing the results of the electrodialysis test of Example 2. [Figure 9] FIG. 9 is a diagram showing the results of an electrodialysis test of a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The cation exchange membrane of the present invention is a cation exchange membrane having a cation exchange layer containing a zeolite having a cation exchange ability and a binder resin, and another cation exchange layer provided on one side or both sides of the cation exchange layer. Zeolite has a crystal structure of an aluminosilicate, has a three-dimensional network structure, and has pores in the three-dimensional network structure. The zeolite in the present invention is not particularly limited, but examples of its crystal structure include LTA type, FER type, MWW type, MFI type, MOR type, LTL type, FAU type, BEA type, etc. The crystal structure is a crystal structure represented by a structure code defined by the International Zeolite Association. In addition, the zeolite in the present invention may be, for example, A type, X type, β type, Y type, L type, ZSM-5 type, MCM-22 type, ferrierite type, modelnite type, etc., and at least one selected from the group consisting of ZSM-5 type, ferrierite type, A type, X type, and Y type is preferable. Zeolite generally has a cation in the crystal structure, and this cation compensates for the negative charge in the crystal structure composed of aluminosilicate to make up for the lack of positive charge. In addition, the cation in the crystal structure is exchanged with another cation, so that the zeolite acts as an ion exchanger. The cation in the crystal structure of the zeolite in the present invention is not particularly limited, but may be, for example, hydrogen ion, lithium ion, calcium ion, sodium ion, potassium ion, magnesium ion, barium ion, etc., and at least one selected from the group consisting of hydrogen ion, lithium ion, calcium ion, sodium ion, and potassium ion is preferable.
[0013] The pore size of the zeolite in the present invention is not particularly limited, but is preferably 0.3 to 1 nm, more preferably 0.4 to 0.8 nm. In addition, examples of the zeolite in the present invention include MFI-type HSZ-800 series, such as 820NHA, Y-type HSZ-300 series, such as 341NHA and 371NHA, LTA-type A-3 series, A-4 series, and A-5 series, LTL-type HSZ-500 series, FAU-type F-9 series, NSA-700 series, MOR-type HSZ-600 series, FER-type HSZ-700 series, Beta-type HSZ-900 series, and MSZ13021 manufactured by ACS Material Co., Ltd. These zeolites may be used after being crushed by a suitable crusher or the like.
[0014] The binder resin in the present invention is not particularly limited as long as it can fix zeolite particles to form a layer or membrane containing zeolite particles. The binder resin in the present invention is preferably one that has no ion exchange capacity or one that has a low ion exchange capacity that is lower than that of conventional ion exchange membranes. In the present invention, a binder resin that has a low ion exchange capacity means one that has an ion exchange group but has a smaller ion exchange capacity than that of conventional ion exchange membranes. The ion exchange group can be, for example, -CF 2 SO 3 H, -SO 3 H, -CF 2 COOH, -COOH, -PO 3 H 2 , -Phenolic OH, -C(CF 3 ) 2 OH, -CF 2 SO 2 Cation exchange groups (anion groups) such as NHR, -N(CH 3 ) 3 OH, -N(CH 2 OH)(CH 3 ) 2 OH, -S(CH 3 ) 2 OH, -P(CH 3 ) 3 OH, -NH2 , -NH, Aniline(NH 2 ) and the like, and anionic and cationic groups described below. The ion exchange capacity when the binder resin has a low ion exchange capacity is preferably 0.001 to 0.2 meq / g, more preferably 0.005 to 0.1 meq / g, more preferably 0.01 to 0.05 meq / g, and even more preferably 0.01 to 0.02 meq / g. In particular, a nonionic resin having no ionic charged group is preferred. When the binder resin has a cation exchange capacity, for example, when it has a cation exchange capacity larger than 0.2 meq / g, the binder resin portion may permeate other cations together with specific cations such as ammonium ions, and the effect of the present invention that the binder resin has excellent selective permeability for ammonium ions may be reduced. When the binder resin has an anion exchange capacity, for example, when it has an anion exchange capacity larger than 0.2 meq / g, it may also permeate anions. In terms of mixing with zeolite particles, the binder resin in the present invention is preferably one that has thermoplasticity and can be dissolved in a general-purpose organic solvent. In addition, it is preferable that the binder resin has excellent dispersibility of zeolite particles. In addition, it is preferable that the binder resin has durability that does not easily decompose. Examples of the binder resin in the present invention include non-ionic resins such as polyethylene, polypropylene, polyethersulfone, polyvinylidene fluoride, polyacrylonitrile, cellulose triacetate, and polyvinyl alcohol.
[0015] In addition, polyolefin may be used as the nonionic binder resin in the present invention. Polyolefin is a polymer of a compound having a double bond in the molecule. Specifically, the polymer may include aliphatic olefin polymers such as the above-mentioned polyethylene, polypropylene, polybutylene, and polybutadiene, aromatic olefin polymers such as polystyrene, polyα-methylstyrene, and polydivinylbenzene, oxygen-containing olefin polymers such as polymethyl methacrylate, polyvinyl acetate, and the above-mentioned polyvinyl alcohol, nitrogen-containing olefin polymers such as the above-mentioned polyacrylonitrile and poly N-methylpyrrolidone, polyvinyl chloride, polyvinylidene chloride, and halogen-containing olefin polymers such as the above-mentioned polyvinylidene fluoride and polytetrafluoroethylene. These polyolefins may be used alone, or a plurality of polyolefins may be mixed. In addition, copolymers or graft copolymers of two or more of the above-mentioned olefins may be used. In addition, nonionic resins such as polyether ketone, polyether ether ketone, polyphenylene, polyphenylene oxide, polyphenylene ether, modified polyphenylene ether, polyphenylene sulfide, and polyetherimide may be used. In the present invention, one type of binder resin may be used, or two or more types may be used. The cation exchange layer in the present invention may contain a third component to increase the dispersibility of zeolite particles in the binder resin. Since the binder resin in the present invention is preferably a nonionic resin, the third component is also preferably nonionic. When the binder resin or the third component has a cation exchange ability, if the binder resin portion permeates other cations as well as specific cations such as ammonium ions, the effect of the present invention, which is excellent in the selective permeability of ammonium ions, may be reduced. When the binder resin or the third component has an anion exchange ability, there is a risk that anions may also be permeated.However, in order to enhance the dispersibility of zeolite, a binder resin may be used in which a cation exchange group or anion exchange group has been introduced so that the binder resin has an ion exchange capacity to an extent that other cations and anions are less likely to permeate along with specific cations such as ammonium ions, or a polymer having a cation exchange group or anion exchange group may be mixed into the binder resin.
[0016] The cation exchange layer containing zeolite and a binder resin in the present invention is a cation exchange layer in which zeolite particles are dispersed in a binder resin. The cation exchange layer in the present invention is not particularly limited as long as it is a layer in which zeolite particles are fixed by a binder resin. For example, the zeolite particles may be fixed by embedding all or a part of the surface of the zeolite particles in the binder resin, or the zeolite particles may be fixed by filling the spaces between the zeolite particles with the binder resin. The cation exchange layer in the present invention may be composed of only zeolite and a binder resin, or may contain components other than zeolite and a binder resin. The cation exchange membrane of the present invention may contain other cation exchange layers described later in addition to the cation exchange layer containing zeolite and a binder resin, and may contain a support or the like.
[0017] The ratio of the content of the zeolite and the binder resin in the cation exchange layer containing the zeolite and the binder resin in the present invention is not particularly limited, but the mass ratio of the zeolite to the binder resin is preferably 0.2:1 to 5:1, preferably 0.5:1 to 3:1, preferably 0.75:1 to 3:1, and more preferably 1:1 to 2:1. That is, the mass ratio of the zeolite to the mass of the binder resin is preferably 0.2 to 5, preferably 0.5 to 3, more preferably 0.75 to 3, and even more preferably 1 to 2. If the content of the zeolite is smaller than the lower limit of the preferred range of the mass ratio, the membrane resistance may be high and the selective permeability of monovalent cations, particularly ammonium ions, may be reduced. On the other hand, if the content of the zeolite is larger than the upper limit of the preferred range of the mass ratio, the selective permeability of the ammonium ions, in particular, may be reduced, and the mechanical strength of the membrane may be reduced. The particle size of the zeolite particles contained in the cation exchange layer in the present invention is not particularly limited, but may be, for example, 0.04 to 5 μm as a crystallite size or primary particle size. Zeolite particles exist not only as crystallites or primary particles, but also as secondary particles aggregated to a certain extent, and the average particle size can be obtained, for example, based on particle size distribution measurement by dynamic light scattering. The average particle size by dynamic light scattering is preferably 0.04 to 5 μm, more preferably 0.1 to 3 μm, and even more preferably 0.5 to 2 μm. Zeolite exists as secondary particles aggregated to a certain extent in the cation exchange layer, and the particle size of the constituent particles when the secondary particles are aggregated and exist as aggregates can be obtained by observation with a scanning electron microscope (SEM). The shape of the constituent particles can be amorphous, approximately elliptical, approximately spherical, etc., so here, the length of the line at the maximum length when a straight line is drawn between two points on the outer edge of the particle in an SEM image is referred to as the particle size.When the average particle size of the constituent particles is obtained from the SEM image, the arithmetic mean diameter of the particle sizes of a plurality of constituent particles can be used, and the number of constituent particles for obtaining the average particle size may be selected as a number suitable for expressing the average of the constituent particles according to the variation of the particle sizes of the constituent particles, and the minimum number for this purpose may be, for example, 10, 20, 30, 50, 100, etc. If the average particle size of the secondary particles or the particle size of the constituent particles by the dynamic light scattering method exceeds 5 μm, the area through which ions pass may become narrow, and the membrane resistance may increase, and the membrane surface may become uneven, which may cause the membrane to break starting from there, and the mechanical strength may decrease. The thickness of the cation exchange layer containing the zeolite and the binder resin in the present invention is not particularly limited, but is preferably 5 to 300 μm, and more preferably 10 to 100 μm. If the thickness of the cation exchange layer is too thin, the mechanical strength may decrease, and if it is too thick, the electrical resistance may increase.
[0018] In the cation exchange layer containing zeolite and binder resin, specific cations are separated and concentrated by selectively moving inside the zeolite particles and permeating out of the layer, so it is desirable that the zeolite particles are dispersed in the layer without uneven distribution. In a uniformly dispersed state, as described above, the cation exchange layer contains zeolite particles at a predetermined mass ratio to the binder resin, in other words, at a predetermined content ratio in the cation exchange layer, and adjacent particles contact each other, and cations can pass through the layer while moving through the particles in a so-called daisy-chain state through the contact sites. This is a different condition for the existence of particles from the case where the target ions are adsorbed to the particles in a liquid. Although a certain content ratio of particles in the cation exchange layer is necessary, if the content ratio is too high in the entire layer or in a part of the layer, the binder resin attached to the particles becomes sparse, and one or more gaps where neither particles nor resin exist may be generated. If unintended cations move through the gaps in the cation exchange layer by short-passing, it will hinder the separation and recovery of the intended cations. If anions pass through the gaps in the opposite direction to the cations, it may lead to a decrease in energy efficiency, such as current efficiency. Furthermore, there is a concern that the mechanical strength of the cation exchange layer may be decreased. Therefore, the cation exchange layer containing zeolite and a binder resin is provided with another cation exchange layer, which will be described below.
[0019] The cation exchange membrane of the present invention has another cation exchange layer on one or both sides of the cation exchange layer containing zeolite and a binder resin. Hereinafter, the other cation exchange layer refers to a cation exchange layer that is not a cation exchange layer containing zeolite and a binder resin. In the cation exchange layer containing zeolite and a binder resin, anions may move through the gap formed as described above, and the current efficiency may decrease. Therefore, by forming the other cation exchange layer, the permeation of anions can be prevented and the decrease in the current efficiency can be prevented. Similarly, the inconvenience in the separation and recovery of the target cations caused by the short pass of non-target cations through the gap can be improved. In addition, by forming the other cation exchange layer, the mechanical strength of the ion exchange membrane can be improved. The material of the other cation exchange layer is not particularly limited, and any material that can be used as a cation exchange membrane can be used, but it is preferable that it has high bonding with the binder resin, and furthermore, it is preferable that it has low membrane resistance and high mechanical strength. Examples of materials constituting the other cation exchange layer include sulfonated polyether sulfone and polyvinyl alcohol copolymer. Examples of polyvinyl alcohol copolymers include PVA-b-PSS and PVA-b-VBTAC described in WO2016 / 133170. Other materials for use in the cation exchange layer include the following anionic polymers:
[0020] An anionic polymer is a polymer containing an anionic group (negatively charged group) in the molecular chain, and the anionic group may be contained in any of the main chain, side chain, and terminal. Examples of the anionic group in the anionic polymer include sulfonate groups, carboxylate groups, and phosphonate groups, as well as the above-mentioned anionic groups. Polymers containing functional groups, part of which can be converted to sulfonate groups, carboxylate groups, and phosphonate groups in water, such as sulfonic acid groups, carboxyl groups, and phosphonic acid groups, are also included in the anionic polymer of the present invention. Among these, sulfonate groups are preferred in terms of their large ionic dissociation constant. An anionic polymer may contain only one type of anionic group, or may contain multiple types of anionic groups. In addition, the counter cation of the anionic group is not particularly limited, and examples include hydrogen ions and alkali metal ions. Among these, alkali metal ions are preferred in terms of less corrosion problems of equipment. An anionic polymer may contain only one type of counter cation, or may contain multiple types of counter cations. The anionic polymer used in the present invention may be a polymer consisting of only structural units containing an anionic group, or may be a polymer consisting of both structural units containing an anionic group and structural units not containing an anionic group. In addition, these polymers may have crosslinking properties. The anionic polymer may be one consisting of only one type of polymer, or may contain multiple types of polymers. In addition, it may be a mixture of these polymers containing an anionic group and a polymer not containing an anionic group. For example, a resin having an ion exchange capacity and a nonionic resin may be mixed and used, such as sulfonated polyethersulfone and polyethersulfone.
[0021] The thickness of the other cation exchange layer is not particularly limited, but is preferably 1 to 100 μm, more preferably 2 to 50 μm. If the thickness of the other cation exchange layer is too thin, the mechanical strength may decrease, and if the thickness is too thick, the membrane resistance may become too high. The ratio of the thickness of the cation exchange layer containing zeolite and a binder resin to the thickness of the other cation exchange layer (if the other cation exchange layer is present on both sides, the total thickness of both sides) is preferably 1:0.1 to 1:100, more preferably 1:0.3 to 1:50, and even more preferably 1:0.5 to 1:10. That is, when the thickness of the cation exchange layer containing zeolite and a binder resin is taken as 1, the ratio of the thickness of the other cation exchange layer is preferably 0.1 to 100, more preferably 0.3 to 50, and even more preferably 0.5 to 10.
[0022] The cation exchange membrane of the present invention may have a support. By having a support, the mechanical strength is improved. The support may be in a cation exchange layer containing zeolite and a binder resin, or in another cation exchange layer, or may be on one or both sides of the cation exchange membrane of the present invention. The support is not particularly limited as long as it has openings, and examples thereof include nets, nonwoven fabrics, woven fabrics, various porous membranes, and the like.
[0023] The method for producing the ion exchange membrane of the present invention is not particularly limited, but examples thereof include a method in which zeolite particles, a binder resin, and a solvent are mixed, the zeolite particles are thoroughly dispersed in the mixed solution, and the mixed solution is applied, cast, or the like to remove the solvent to form a membrane. The method for forming the other cation exchange layer is not particularly limited, but examples thereof include a method in which a resin forming the other cation exchange layer is mixed with a solvent, and the mixture is applied onto a cation exchange layer containing zeolite and a binder resin to remove the solvent, and a method in which a cation exchange membrane forming the other cation exchange layer is bonded to a cation exchange layer containing zeolite and a binder resin. The particle size of the zeolite particles used is not particularly limited, but examples thereof include crystallite size or primary particle size of 0.04 to 5 μm. In addition, the zeolite particles used preferably have an average particle size of 0.04 to 5 μm, more preferably 0.1 to 3 μm, and even more preferably 0.5 to 2 μm, as measured by a dynamic light scattering method. When the zeolite particles in the produced cation exchange layer are present as aggregates, it is preferable to disperse the zeolite in the binder resin so that the particle size of the constituent particles is 5 μm or less, or the average particle size of the constituent particles is preferably 0.04 to 5 μm, more preferably 0.1 to 3 μm, and even more preferably 0.5 to 2 μm. When a support is used, for example, a mixed solution of zeolite, binder resin, and solvent is applied to a support such as a net, nonwoven fabric, woven fabric, or porous membrane, and the mixed solution is impregnated into the support or the support is immersed in the mixed solution, and then the solvent is removed to produce a cation exchange membrane having a support. The solvent is not particularly limited, but it is preferable that the binder resin is easily dispersed or dissolved and the zeolite particles are easily dispersed.Examples of the solvent include hydrocarbons such as benzene, xylene, toluene, and hexane; alcohols such as methanol, ethanol, and isopropyl alcohol; ketones such as acetone, methyl isopropyl ketone, and cyclohexane; ethers such as dioxane and tetrahydrofuran; esters such as ethyl acetate and butyl acetate; and nitrogen-containing compounds such as isopropylamine, diethanolamine, N-methylformamide, N,N-dimethylformamide, and dimethyl sulfoxide. At least one of these can be appropriately selected and used.
[0024] In the ion exchange membrane cell of the present invention, an anion exchange membrane and a cation exchange membrane of the present invention are arranged opposite to each other. The anion exchange membrane in the ion exchange membrane cell of the present invention is not particularly limited as long as it is a membrane that selectively permeates anions. FIG. 1 shows an example of the use of the ion exchange membrane cell of the present invention, in which the ion exchange membrane cells of the present invention are stacked for an electrodialysis device. When another cation exchange layer is provided on one side, it is preferable to face the cation exchange layer containing zeolite and a binder resin to the anode side. In the electrodialysis device of FIG. 1, a dilute side solution is passed through the anode side of the cation exchange membrane of the present invention, and a concentrated side solution is passed through the cathode side. A solution containing various ions is introduced into the dilute side, and while the introduced solution passes between the anion exchange membrane and the cation exchange membrane of the present invention, for example, ammonium ions as specific cations in the solution selectively permeate the cation exchange membrane of the present invention and move to the concentrated side. In this way, ammonium ions are concentrated on the concentrated side. Various ions may be present in the dilute side solution, and specific cations can be selectively concentrated by the selectivity of the cation exchange membrane of the present invention. The various cations present in the dilute solution are not particularly limited, but may include, for example, alkali metal ions, alkaline earth metal ions, and other monovalent to trivalent cations, such as ammonium ions, sodium ions, potassium ions, lithium ions, calcium ions, magnesium ions, and hydrogen ions, as well as heavy metal ions such as silver ions, copper, zinc, and mercury. The various anions coexisting with ammonium ions in the dilute solution are not particularly limited, but may include, for example, hydroxide ions, chloride ions, bromine ions, fluorine ions, iodide ions, carbonate ions, nitrate ions, sulfate ions, and phosphate ions. The solution introduced into the concentrate is not particularly limited, but may include, for example, raw water to be concentrated, water in which specific ions in the raw water are concentrated, or water, and may contain the various ions contained in the dilute solution. Tap water, industrial water, pure water, etc. can be used as the water. In the electrodialysis apparatus of FIG. 1, illustrations of a gasket with a mesh disposed between the ion exchange membranes, a power source for supplying power to the anode and cathode, piping for supplying solutions to the dilution side and concentration side, a pump, etc. are omitted.For example, those generally used in electrodialysis devices can be used.
[0025] In the cation exchange membrane and electrodialysis apparatus of the present invention, when another cation exchange layer is provided on one side, the effect of preventing the movement of anions from the cathode side to the anode side can be further improved by facing the cation exchange layer containing zeolite and a binder resin to the anode side, i.e., by facing the other cation exchange layer to the cathode side, the current efficiency can be increased. On the other hand, when the cation exchange layer containing zeolite and a binder resin is faced to the cathode side, i.e., when the other cation exchange layer is faced to the anode side, if the specific cation is ammonium ion, cations other than ammonium ion are distributed in high concentration in the other cation exchange layer, so that the selectivity for ammonium ion may be reduced, and the blocking ability of anions may be reduced compared to when the other cation exchange layer is faced to the cathode side. EXAMPLES
[0026] The present invention will be specifically described below by way of examples of the present invention, but the technical scope of the present invention is not limited to these examples.
[0027] The polymers, adsorbents, and ion exchange membranes used in the examples and comparative examples were prepared as follows. 1. Polyethersulfone (Sumikaexcel PES (grade: 5900P), manufactured by Sumitomo Chemical Co., Ltd.; hereinafter referred to as PES) 2. Sulfonated polyethersulfone (EW0710, manufactured by Konishi Chemical Industry Co., Ltd., hereinafter referred to as SPES) 3. Zeolite (HSZ (registered trademark) 820NHA, manufactured by Tosoh Corporation) 4. Standard cation exchange membrane Neosepta (registered trademark) CSE (manufactured by Astom Corporation)
[0028] [Example 1] PES was added to N,N-dimethylacetamide (DMAc) so that the concentration of PES was 20% by mass, and dissolved by stirring with a magnetic stirrer while heating to 60°C in an oil bath. Zeolite particles were added to a DMAc solution of PES prepared so that the mass ratio of zeolite:PES was 3:1, and mixed with a magnetic stirrer for 1 hour to disperse the zeolite particles in the DMAc solution of PES. Then, it was degassed for 10 minutes in an ultrasonic bath. The solution thus obtained was applied to a glass plate using a film applicator (Cortic Co., Ltd., KT-3405) with the applicator set to a height of 0.3 mm, and molded into a film. Then, it was dried on a hot plate at 60°C for 30 minutes to evaporate a part of the DMAc. Meanwhile, SPES was added to DMAc and dissolved so that the concentration of SPES was 20% by mass. A solution of SPES dissolved in DMAc was dripped onto the film containing the previously dried zeolite, and applied using a film applicator. After coating, the glass plate was dried on a hot plate at 60°C for 1 hour or more to evaporate the DMAc, and a membrane (hereinafter also referred to as a composite membrane) having a cation exchange layer containing zeolite and a cation exchange layer made of SPES was obtained. The composite membrane obtained was immersed in ion-exchanged water and peeled off from the glass plate. In addition, an image of the zeolite particles used (zeolite particles before being added to the DMAc solution of PES) observed with a scanning electron microscope (SEM) is shown in Figure 2. The zeolite particles were aggregated and the particle size was unclear. On the other hand, the average particle size of the zeolite particles used was measured by dynamic light scattering (using ELSZ-2000 manufactured by Otsuka Electronics) and was 1.1 μm. The average particle size (hydrodynamic diameter) was measured by performing cumulant analysis on the particle size distribution obtained by dispersing a slurry of zeolite powder in distilled water to a concentration of 1 g / L at a measurement temperature of 25°C and 25 cumulative times.
[0029] [Reference example] A solution in which zeolite particles were dispersed in a DMAc solution of PES was prepared in the same manner as in Example 1. The prepared solution was applied to a glass plate in the same manner as in Example 1 and formed into a film. Thereafter, the solution was dried on a hot plate at 60°C for 1 hour to evaporate the DMAc, thereby obtaining a membrane containing zeolite (hereinafter also referred to as a zeolite membrane). The obtained membrane was immersed in ion-exchanged water and peeled off from the glass plate.
[0030] [Comparative Example] As Comparative Example 1, a standard cation exchange membrane, CSE, manufactured by Astom Corporation, was used.
[0031] (SEM observation of a cation exchange layer containing zeolite) For ease of observation, the state of zeolite in the cation exchange layer was observed using a zeolite membrane of a reference example prepared in the same manner as the cation exchange layer containing zeolite in Example 1. FIG. 3 shows an image of a cross section of a zeolite membrane observed by a scanning electron microscope (SEM). Several parts that look like sponge-like cavities were observed in the cross section as a whole. These parts can be said to be gaps where neither particles nor binders exist. Zeolite became aggregate particles whose secondary particle size was difficult to distinguish due to the binder PES. From this image, the particle size of the zeolite particles constituting the aggregate particles observed by SEM was a minimum of 0.1 μm and a maximum of about 0.3 μm, and the average particle size of the constituent particles of the zeolite constituting the aggregate particles was approximately 0.2 μm. It is considered that particles of these sizes contain particles of approximately crystal size. (a) to (c) in FIG. 3 are images measured at different magnifications. Figure 3(c) is an enlarged image of the square frame in Figure 3(b), where the white circles indicate examples of zeolite particles that make up the aggregate particles. The diameter of the openings that appear to be hollows was in the range of approximately 1 to 10 μm.
[0032] (Film thickness measurement) The thickness of the resulting film was measured using a film thickness meter (ABS Digimatic Blade Thickness, Mitutoyo Corporation).
[0033] (Measurement of membrane resistance) The measurement device and conditions for the membrane resistance are shown in Figure 4. First, an acrylic cell with a platinum electrode (current carrying area 0.949 cm 2 ) as the measurement solution. 4 Cl aqueous solution (NH 4 The solution resistance (R 0 ) was measured. Then, a sample membrane was placed between the two cells, and the resistance was measured in the same manner. The membrane resistance (R 1 ) is calculated from the following formula (1), and the membrane resistance obtained is divided by the membrane thickness to obtain the membrane specific resistance K from formula (2). m [Ωcm] was calculated. In the formula (1), R 1 [Ωcm 2 ] is the resistance measured by sandwiching the sample film between two cells, and R 0 [Ωcm 2 ] is the solution resistance measured without the sample film, and R m [Ωcm 2 ] is the membrane resistance. In equation (2), K m [Ωcm] is the film resistivity and d [cm] is the film thickness.
[0034]
number
[0035]
number
[0036] (Electrodialysis) As shown in Figure 5, the effective membrane area is 4.0 cm 2 The measurement membrane was sandwiched between the (2.0 cm × 2.0 cm) device and incubated at 25°C in 0.1 M NH 4 Cl, 0.1M NaCl and 0.1M CaCl 2 The mixed salt solution was placed in two cells, and electrodialysis was performed between the Ag·AgCl electrodes at a constant current of 90 mA using a DC stabilized power supply (PMC35-2A, Kikusui Electronics Co., Ltd.) for approximately 120 minutes. The solution in the cells was sampled at regular intervals. After that, the NH4 + , Na + and Ca 2+ The concentration of these ions was quantified to measure the change in concentration over time. The flux of each ion was calculated from these values using the following formula. In formula (3), J i [mol m -2 ·s -1 ] represents the permeation flow rate, and V [m 3 ] represents the volume of the concentrated solution, and S [m 2 ] represents the effective membrane area, t [s] represents the time during which the current was passed, and ΔC i / Δt [mol m -3 ·s -1 ] represents the initial concentration gradient. Also, i is NH 4 + , Na + or Ca 2+ In formulas (4) and (5), P NH4 Na and P NH4 Ca represents the ion selective permeability coefficient [-]. In equation (6), η [-] represents the current efficiency, and z i [-] represents the valence of the cation, I [A] represents the electric current, and F [C mol -1 ] represents the Faraday constant.
[0037]
number
[0038]
number
[0039]
number
[0040]
number
[0041] (Reference measurement results) The thickness of the zeolite membrane obtained in the reference example was 77 μm, and the membrane resistivity of this membrane was 77 Ω cm. The results of electrodialysis using this membrane are shown in Figure 6. This figure shows the NH 4 + , Na + and Ca 2+ The graph shows the time change in ion concentration on the concentrated side and diluted side of the ion. All three types of cations move from the diluted side to the concentrated side due to the applied DC voltage. The permeation flux was calculated from the slope of the time-concentration curve using equation (3), and the ion selectivity coefficient was calculated using equations (4) and (5). As a result, P NH4 Na becomes 2.07, and P NH4 Ca became 2.33. This is Na + 2.07 times more NH 4 + This indicates that Ca selectively permeated the 2+ 2.33 times more NH 4 + This shows that the selective permeation of the electrons occurred with a current efficiency of 0.46.
[0042] (Measurement results for comparative examples) The thickness of the cation exchange membrane of the comparative example was 160 μm, and the membrane resistivity was 113 Ωcm. Electrodialysis was performed using the cation exchange membrane of the comparative example. The results are shown in FIG. NH4 Na is 1.81, and P NH4 Ca was 0.98. This is Na + 1.81 times more NH 4 + This indicates that selective permeation of P NH4 Ca Since the value of is less than 1, NH 4 + Ca 2+It is shown that the zeolite membrane of the Reference Example selectively permeated 1.02 times as much ammonium ions. The current efficiency at this time was 0.97. It is seen from the Reference Example and Comparative Example that the zeolite membrane of the Reference Example exhibited higher selective permeability to ammonium ions than the cation exchange membrane of the Comparative Example, but was inferior in current efficiency.
[0043] (Measurement results of Example 1) In the composite membrane obtained in Example 1, the thickness of the zeolite membrane was 86 μm, the thickness of the SPES membrane was 40 μm, and the combined thickness of the two was 126 μm. The specific resistance of the entire membrane was 181 Ωcm. The results of electrodialysis using this membrane with the zeolite membrane facing the anode are shown in FIG. 8. This figure shows the results of electrodialysis using NH 4 + , Na + and Ca 2+ The graph shows the time change in ion concentration on the concentrated side and diluted side of the ion. All three types of cations move from the diluted side to the concentrated side due to the applied DC voltage. The permeation flux was calculated from the slope of the time-concentration curve using equation (3), and the ion selectivity coefficient was calculated using equations (4) and (5). As a result, P NH4 Na becomes 2.10, and P NH4 Ca was 2.17. This is Na + 2.10 times more NH 4 + This indicates that Ca selectively permeated the 2+ 2.17 times more NH 4 + The current efficiency at this time was 0.90, which shows an ion selectivity coefficient similar to that of the reference example, but is about twice as high as the reference example. This is believed to be because the SPES layer suppresses the permeation of anions.
[0044] [Example 2] In Example 2, the composite membrane obtained in Example 1 was placed so that the zeolite membrane side faced the cathode, and electrodialysis was carried out. The results are shown in Figure 9. This figure shows the results of electrodialysis using NH 4 + , Na +and Ca 2+ The graph shows the time change in ion concentration on the concentrated side and diluted side of the ion. All three types of cations move from the diluted side to the concentrated side due to the applied DC voltage. The permeation flux was calculated from the slope of the time-concentration curve using equation (3), and the ion selectivity coefficient was calculated using equations (4) and (5). As a result, P NH4 Na is 1.84, and P NH4 Ca was 2.89. This is Na + 1.84 times more NH 4 + This indicates that Ca selectively permeated the 2+ 2.89 times more NH 4 + In addition, the current efficiency at this time was 0.92, which was approximately twice as high as that of the reference example. [Industrial Applicability]
[0045] The cation exchange membrane of the present invention has excellent selective permeability, particularly for ammonium ions, and can be used in various applications for concentrating ammonium ions, such as in various water treatments for wastewater, etc. The cation exchange membrane of the present invention can also be suitably used in electrodialysis devices, Donnan dialysis devices, etc.
Claims
1. A cation exchange membrane comprising a cation exchange layer containing zeolite and a binder resin, and another cation exchange layer provided on one or both sides of the cation exchange layer.
2. 2. The cation exchange membrane according to claim 1, wherein the binder resin is a resin having no ion exchange capacity and / or a resin having a low ion exchange capacity.
3. 3. An ion exchange membrane cell comprising an anion exchange membrane and the cation exchange membrane according to claim 1 or 2 disposed opposite each other.
4. 3. An electrodialysis apparatus comprising an anode, a cathode, a cation exchange membrane and an anion exchange membrane, wherein the cation exchange membrane is the cation exchange membrane according to claim 1 or 2.
Citation Information
Patent Citations
Method and system for simultaneously recovering ammonia component and phosphorus component in water to be treated
JP2011092822A
